La violencia intrafamiliar y su influencia en el rendimiento académico de los estudiantes de la Escuela Eloy Alfaro de la parroquia El Cambio del cantón Machala durante el periodo 2012-2013. - Zhiñin Gordillo, Clemencia Angelita (2013)
This research takes as its object of study domestic violence as a fact presented through various manifestations, based on motivations related to the dysfunctionality facing contemporary society, whose effects become evident specifically on children and youth in process training.